The production of antioxidants via solid substrate fermentation using Lentinus Squarrosulus (Mont.) / Siti Marjiana Ismail - Siti Marjiana, Ismail (2011)
In this study, antioxidants extracted, using methanol and dichloromethane, from Lentinus squarrosulus (Mont.) mycelium grown on rice, maize and soya bean supplemented with nitrogen sources (malt extract, yeast extract and peptone) at various concentrations were compared with mycelium grown in liquid Glucose-Yeast-Malt-peptone (GYMP). The antioxidant capacity of the extracts were then analyzed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging abilities and inhibition of lipid peroxidation. The total phenol content (TPC) of the extracts was also measured using the Folin–Ciocalteu method. It was found that antioxidants from L. squarrosulus grown on maize supplemented with 0.04% peptone extracted with methanol gave the best DPPH scavenging activity with IC50 23.5mg/ml compared to L. squarrosulus grown in liquid GYMP and unfermented maize with IC50 of 26.9mg/ml and 29.8mg/ml respectively. Positive control, ascorbic acid exhibited fast reaction kinetics compared to quercetin dihydrate and BHA with intermediate to slow reaction kinetics in scavenging DPPH radicals with IC50 values of 0.078mg/ml (0.1mM), 0.032mg/ml (0.2mM) and 0.107mg/ml (1.0mM) respectively as opposed to the moderate reaction kinetics exhibited by the L. squarrosulus extracts. The selected methanolic antioxidant extract of L. squarrosulus fermented maize was further analyzed for the inhibition of lipid peroxidation using egg yolk and cooking oil. The IC50 values using egg yolk showed methanolic extract of maize fermented with L. squarrosulus exhibited 1.62mg/ml as opposed to 2.00mg/ml for L. squarrosulus grown in liquid GYMP and 23.5mg/ml for unfermented maize. The IC50 values of quercetin dihydrate, BHA and ascorbic acid were 0.07mg/ml, 0.085mg/ml and 0.10mg/ml respectively. In lipid peroxidation of cooking oil, the L. squarrosulus fermented maize extracts showed increasing inhibition of lipid peroxidation activity when the concentration was increased as opposed to L. squarrosulus grown in liquid GYMP. Addition of 1.0mg/ml and 5.0mg/ml L. squarrosulus fermented maize extracts in the cooking palm oil reduced 53.0% and 64.8% of lipid peroxidation which occurred upon heating. The TPC values of unfermented maize was the lowest with total phenolic content 15.40mgGAE/g extract compared to L. squarrosulus grown in liquid GYMP with 31.39mgGAE/g extract and 19.34mgGAE/g extract for maize fermented with L. squarrosulus. In conclusion, L. squarosulus has the potential to produce antioxidants to be used as dietary supplements or food preservatives by solid substrate fermentation on maize supplemented with 0.04% peptone.